2003
DOI: 10.1042/cs20030010
|View full text |Cite
|
Sign up to set email alerts
|

T wave peak-to-end interval and QT dispersion in acquired long QT syndrome: a new index for arrhythmogenicity

Abstract: QT dispersion (QTD) on 12-lead ECGs has been proposed as a marker of malignant ventricular tachyarrhythmias, and increased QTD has been reported in long QT syndrome (LQTS). On the other hand, it has been demonstrated that transmural dispersion is associated with ventricular tachyarrhythmias in an experimental model. However, the precise type of QTD or transmural dispersion that contributes most to ventricular tachyarrhythmias in patients with LQTS remains unclear. We evaluated 27 patients with acquired LQTS. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
209
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(217 citation statements)
references
References 23 publications
4
209
1
3
Order By: Relevance
“…Previous studies have shown that prolongation of the Tp-e interval is associated with increased mortality in Brugada syndrome, hypertrophic cardiomyopathy, and in patients undergoing primary percutaneous coronary intervention for myocardial infarction [13,22,23]. Yamaguchi et al [24] found that the Tp-e/QT ratio is a superior predictor of torsades de pointes than either QTc interval or QTd in patients with long QT syndrome (LQTS). Likewise, QTc did not reach statistical significance between the two groups in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that prolongation of the Tp-e interval is associated with increased mortality in Brugada syndrome, hypertrophic cardiomyopathy, and in patients undergoing primary percutaneous coronary intervention for myocardial infarction [13,22,23]. Yamaguchi et al [24] found that the Tp-e/QT ratio is a superior predictor of torsades de pointes than either QTc interval or QTd in patients with long QT syndrome (LQTS). Likewise, QTc did not reach statistical significance between the two groups in our study.…”
Section: Discussionmentioning
confidence: 99%
“…2) [78,81]. A prolonging of the TpTe interval to .100 ms is proposed to be associated with increased vulnerability for the occurrence of early after-depolarisations and, thus, ventricular tachycardia and SCD [82][83][84].…”
Section: Ventricular Repolarisation Disturbancesmentioning
confidence: 99%
“…QTc interval was the QT interval corrected with the Bazett's formula (QT/√RR) (16). Besides, Tp-e was defined as the interval from the peak of a positive T wave or the nadir of a negative T wave to the end of the T wave in the tail method (17). In the tangent method, Tp-e (Tp-e tangent) was defined as the time from the peak of the T wave to the intersection between the tangent line and the isoelectric line (9, 18) ( Figure 1).…”
Section: Electrocardiographymentioning
confidence: 99%